Secondary battery and electric device

By controlling the silicon content and the mass ratio of silane compounds to lithium nickel transition metal oxides in the CEI film, a dense interface film is formed, which solves the structural instability problem of high-nickel lithium-ion batteries and improves the high-temperature performance and cycle life of the battery.

CN116632351BActive Publication Date: 2026-11-06NIO BATTERY TECH (ANHUI) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310789302.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-29
Publication Date
2026-11-06
Estimated Expiration
2043-06-29

AI Technical Summary

Technical Problem

The unstable cathode structure of high-nickel lithium-ion batteries leads to safety hazards and reduced battery performance, especially under high-temperature conditions.

Method used

By controlling the silicon content in the solid electrolyte interphase (CEI) film on the surface of the positive electrode active material layer and the mass ratio of silane compounds to nickel in lithium nickel transition metal oxides, the amount of silane compounds can be adjusted to form a dense interphase film, thereby inhibiting nickel dissolution and improving the high-temperature performance and cycle life of the battery.

Benefits of technology

It effectively inhibits the leaching of nickel from the positive electrode active material layer, improves the battery's high-temperature performance, power performance, and cycle performance, while reducing structural damage to the negative electrode sheet and enhancing the battery's safety and cycle performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_8
    Figure SMS_8
  • Figure SMS_9
    Figure SMS_9
  • Figure QLYQS_1
    Figure QLYQS_1
Patent Text Reader

Abstract

This application relates to secondary batteries and devices. The secondary battery of this application includes a positive electrode, a negative electrode, and an electrolyte, wherein the electrolyte includes a silane compound; the positive electrode includes a positive active material layer and a solid electrolyte interface (CEI) membrane located on the surface of the positive active material layer, and the mass percentage of silicon in the CEI membrane is A% as measured by energy dispersive spectroscopy; the positive active material layer includes lithium nickel transition metal oxide, and the content of the silane compound is 1g relative to Bg of nickel in the positive active material layer; wherein 0.2≤100×A / B≤10. By controlling the silicon content in the CEI membrane and the mass ratio of the silane compound to the nickel in the lithium nickel transition metal oxide, the secondary battery of this application effectively suppresses the dissolution of nickel, enabling the nickel-containing positive electrode secondary battery to possess excellent high-temperature performance, low impedance, and long cycle life while improving battery capacity and energy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of energy storage. Specifically, this application relates to a secondary battery and an electrical device. Background Technology

[0002] Lithium-ion batteries, due to their high specific energy and safety, have been widely used in portable electronic devices, electric vehicles, and high-tech fields. To meet the needs of societal development, higher capacity and greater safety are the main research topics for lithium-ion batteries. High-nickel cathode systems can effectively improve battery capacity / energy, but increasing the nickel content in the cathode reduces the stability of the cathode structure, thereby increasing safety risks. Summary of the Invention

[0003] To address the shortcomings of existing high-nickel lithium-ion batteries, this application provides a secondary battery and related device. The secondary battery of this application effectively suppresses the dissolution of nickel from the positive electrode active material layer by controlling the silicon content in the solid electrolyte interphase (CEI) film formed on the surface of the positive electrode active material layer and the mass ratio of silane compounds to nickel in the lithium nickel transition metal oxide. This results in a secondary battery with a nickel-containing positive electrode that, while improving battery capacity and energy, also possesses excellent high-temperature performance, low impedance, and long cycle life.

[0004] The first aspect of this application provides a secondary battery comprising a positive electrode, a negative electrode, and an electrolyte, wherein the electrolyte comprises a first additive, which is a silane compound; the positive electrode comprises a positive active material layer and a solid electrolyte interface film located on the surface of the positive active material layer, and the mass percentage of silicon in the solid electrolyte film is A% as measured by energy dispersive spectroscopy (EDS); the positive active material layer comprises a lithium nickel transition metal oxide, and the content of the silane compound is 1 g relative to B g of nickel in the positive active material layer; wherein 0.2 ≤ 100 × A / B ≤ 10.

[0005] The inventors of this application discovered through research that by controlling the silicon content of the silane compound additive in the positive electrode CEI film and the mass ratio of the silane compound to the nickel in the lithium nickel transition metal oxide, the amount of silane compound used in different nickel-containing positive electrodes can be effectively controlled. This allows the silane compound additive to fully exert its high-temperature performance enhancement effect, while avoiding the disadvantage of high interfacial impedance caused by excessive silicon content in the CEI film. As a result, the battery possesses excellent high-temperature performance and safety, as well as good power performance and cycle performance.

[0006] A second aspect of this application provides an apparatus comprising the secondary battery described in the first aspect.

[0007] The beneficial effects of this application are as follows:

[0008] This application's secondary battery fully leverages the high-temperature performance enhancement effect of silane compounds on different nickel-containing cathodes by controlling the silicon content in the CEI film and the mass ratio of silane compounds to nickel in lithium nickel transition metal oxides. At the same time, it avoids the disadvantage of high interfacial impedance caused by excessive silicon content in the CEI film, effectively suppresses the dissolution of nickel in the positive electrode active material layer, reduces structural damage to the negative electrode sheet, and improves the cycle performance of the secondary battery. Detailed Implementation

[0009] For the sake of brevity, this application only specifically discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, just as any upper limit can be combined with any other upper limit to form an unspecified range. Furthermore, each individually disclosed point or single value can itself serve as a lower or upper limit and be combined with any other point or single value or with other lower or upper limits to form an unspecified range.

[0010] Unless otherwise stated, the terms used in this application have their common meanings as commonly understood by those skilled in the art. Unless otherwise stated, the values ​​of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (e.g., they can be tested according to the methods given in the embodiments of this application).

[0011] The list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms can mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another instance, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.

[0012] The present application will be further described below with reference to specific embodiments. It should be understood that these specific embodiments are for illustrative purposes only and are not intended to limit the scope of the present application.

[0013] Primary and secondary batteries

[0014] The secondary battery provided in this application includes a positive electrode, a negative electrode, and an electrolyte. The electrolyte includes a first additive, which is a silane compound. The positive electrode includes a positive active material layer and a solid electrolyte interface film located on the surface of the positive active material layer. Using an energy dispersive spectroscopy (EDS) instrument, the mass percentage of silicon in the solid electrolyte film is A%. The positive active material layer includes a lithium-nickel transition metal oxide. For every B g of nickel in the positive active material layer, the content of the silane compound is 1 g. Wherein, 0.2 ≤ 100 × A / B ≤ 10. If the A / B ratio is too high, the mass percentage of silicon in the solid electrolyte interfacial film is too high, or the content of nickel relative to silane compounds in the positive electrode active material is too low. An excessively high mass percentage of silicon in the solid electrolyte interfacial film means that there is too much silicon-containing compound in the positive electrode solid interfacial film. This non-conductive silicon-containing organic compound will significantly increase the interfacial impedance, increase battery polarization, thereby accelerating the battery capacity decay and deteriorating cycle performance and power performance. An excessively low content of nickel relative to silane compounds in the positive electrode active material will affect the battery capacity and energy. If the A / B ratio is too small, the mass percentage of silicon in the solid electrolyte interface film will be too low, or the content of nickel relative to silane compounds in the positive electrode active material will be too high. A low mass percentage of silicon in the solid electrolyte interface film means that there is too little silicon-containing compound in the positive electrode solid interface film, insufficient to form a dense three-dimensional network interface film to effectively protect the positive electrode side. This leads to increased nickel dissolution, increasing structural damage to the negative electrode sheet and affecting the battery's high-temperature safety and cycle performance. Conversely, an excessively high content of nickel relative to silane compounds in the positive electrode active material, i.e., an excessively high nickel content in the lithium-nickel transition metal oxide, will lead to lithium-nickel mixing, causing lithium deposition and worsening the battery's high-temperature safety. It will also increase nickel dissolution during deep cycling. The dissolved nickel deposits on the negative electrode side, damaging the negative electrode structure and accelerating the decay of the battery's cycle capacity.

[0015] In some implementations, 100×A / B is exemplarily a range of 0.2, 0.4, 0.5, 0.6, 0.8, 1, 1.2, 1.4, 1.5, 1.6, 1.8, 2, 2.2, 2.4, 2.6, 2.8, 3, 3.2, 3.4, 3.6, 3.8, 4, 4.2, 4.4, 4.6, 4.8, 5, 5.2, 5.4, 5.6, 5.8, 6, 6.2, 6.4, 6.6, 6.8, 7, 7.2, 7.4, 7.6, 7.8, 8, 8.2, 8.4, 8.6, 8.8, 9, 9.2, 9.4, 9.6, 9.8, 10, or any combination of these values. In some implementations, 0.5 ≤ 100×A / B ≤ 8.

[0016] In some implementations, 0.8 ≤ A ≤ 8. In some implementations, A is exemplarily a range of 0.8, 1, 1.2, 1.4, 1.6, 1.8, 2, 2.2, 2.4, 2.6, 2.8, 3, 3.2, 3.4, 3.6, 3.8, 4, 4.2, 4.4, 4.6, 4.8, 5, 5.2, 5.4, 5.6, 5.8, 6, 6.2, 6.4, 6.6, 6.8, 7, 7.2, 7.4, 7.6, 7.8, 8, or any combination of these values. In some implementations, 2 ≤ A ≤ 7.

[0017] In some implementations, 60 ≤ B ≤ 700. B is exemplarily a range of 60, 80, 100, 120, 140, 150, 160, 180, 200, 220, 240, 250, 260, 280, 300, 320, 340, 350, 360, 380, 400, 420, 450, 480, 500, 520, 550, 580, 600, 620, 650, 680, 700, or any combination of these values. In some implementations, 100 ≤ B ≤ 600. In some implementations, 100 ≤ B ≤ 500.

[0018] The secondary battery provided in this application includes a positive electrode, a negative electrode, and an electrolyte. The secondary battery undergoes formation. The electrolyte includes a first additive, which is a silane compound. The positive electrode includes a positive active material layer and a solid electrolyte interface film located on the surface of the positive active material layer. Using energy dispersive spectroscopy (EDS), the mass percentage of silicon in the solid electrolyte film is A%. The positive active material layer includes a lithium-nickel transition metal oxide. For every B g of nickel in the positive active material layer, the content of the silane compound is 1 g. Wherein, 0.2 ≤ 100 × A / B ≤ 10.

[0019] In this application, the solid electrolyte membrane is a non-artificial membrane. In some embodiments, the solid electrolyte interface membrane is formed by the reaction of the positive electrode active material with the electrolyte. In some embodiments, the silicon element in the solid electrolyte interface membrane is derived from silane compounds.

[0020] In this application, the mass percentage of silicon in the solid electrolyte interface film refers to the mass percentage of silicon in the entire solid electrolyte interface film region on the surface of the positive electrode active material layer, not the mass percentage of silicon in the interface film within a certain depth region of the interface film at a distance from the interface film and electrolyte side, but rather the mass percentage of silicon in the interface film throughout the entire depth region of the interface film. In this application, the mass percentage of silicon in the solid electrolyte interface film refers to the mass percentage of silicon in the interface film relative to the mass percentage of all elements from Be to U.

[0021] In this application, the mass percentage of silicon in the solid electrolyte interface film is detected using EDS. EDS utilizes the different energies of X-ray quanta, which are received by a detector and output as electrical pulse signals. These signals are amplified and shaped by an amplifier before being sent to a multichannel pulse analyzer. The pulse number and pulse height curves are then displayed on a cathode ray tube. With an energy resolution of 132 eV, it can detect the elemental content from Be to U.

[0022] In some embodiments, the silane compound includes at least one of the compounds represented by Formula I.

[0023] Formula I

[0024] In Formula I, R1, R2, R3, and R4 are independently selected from substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C1-C6 alkoxy, substituted or unsubstituted C2-C6 alkenyl, substituted or unsubstituted C2-C6 alkenyl, substituted or unsubstituted C2-C6 alkynyl, and substituted or unsubstituted C2-C6 alkynyl, and at least one of R1, R2, R3, and R4 is selected from substituted or unsubstituted C2-C6 alkenyl, substituted or unsubstituted C2-C6 alkenyl, substituted or unsubstituted C2-C6 alkynyl, and substituted or unsubstituted C2-C6 alkynyl. In some embodiments, when substituted, the substituent is independently selected from halogens. In some embodiments, when substituted, the substituent is fluorine.

[0025] In this application, C1-C6 alkyl groups include, but are not limited to, methyl, ethyl, n-propyl, isopropyl, cyclopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, cyclobutyl, n-pentyl, isopentyl, neopentyl, cyclopentyl, n-hexyl, isohexyl, and cyclohexyl.

[0026] C1-C6 alkoxy groups include, but are not limited to: methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, isobutoxy, tert-butoxy, n-pentoxy, isopentoxy, and n-hexyloxy.

[0027] C2-C6 alkenyl groups include, but are not limited to: vinyl, propenyl, allyl, isopropenyl, n-butenyl, isobutenyl, tert-butenyl, n-pentenyl, isopentenyl, hexenyl, and cyclohexenyl.

[0028] C2-C6 olefins include, but are not limited to: ethyleneoxy, allyloxy, propenoxy, isopropenoxy, n-butenoxy, isobutenoxy, tert-butenoxy, pentenoxy, isopentenoxy, hexenoxy, and cyclohexenoxy.

[0029] C2-C6 alkynyl groups include, but are not limited to: ethynyl, n-propynyl, isopropynyl, n-butynyl, isobutynyl, n-pentynyl, isopentenynyl, and hexynyl.

[0030] C2-C6 alkynyloxy groups include, but are not limited to: ethynyloxy, n-propynyloxy, isopropynyloxy, n-butynyloxy, isobutynyloxy, n-pentynyloxy, isopentynyloxy, and hexynyloxy.

[0031] Halogens include fluorine, chlorine, bromine, and iodine.

[0032] In some embodiments, R1, R2, R3, and R4 are independently selected from substituted or unsubstituted C1-C4 alkyl, substituted or unsubstituted C1-C4 alkoxy, substituted or unsubstituted C2-C4 alkenyl, substituted or unsubstituted C2-C4 alkenyl, substituted or unsubstituted C2-C4 alkynyl, and substituted or unsubstituted C2-C4 alkynyl, and at least one of R1, R2, R3, and R4 is selected from substituted or unsubstituted C2-C4 alkenyl, substituted or unsubstituted C2-C4 alkenyl, substituted or unsubstituted C2-C4 alkynyl, and substituted or unsubstituted C2-C4 alkynyl. In some embodiments, when substituted, the substituent is independently selected from halogens. In some embodiments, when substituted, the substituent is fluorine.

[0033] In some embodiments, R1 is selected from substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C1-C6 alkoxy, and R2, R3, and R4 are independently selected from substituted or unsubstituted C2-C6 alkenyl, substituted or unsubstituted C2-C6 alkenyloxy, substituted or unsubstituted C2-C6 alkynyl, and substituted or unsubstituted C2-C6 alkynyloxy. When substituted, the substituent is independently selected from halogens. In some embodiments, the alkyl, alkoxy, alkenyl, alkenyloxy, alkynyl, and alkynyloxy groups are C1-C4 alkyl, C1-C4 alkoxy, C2-C4 alkenyl, C2-C4 alkenyloxy, C2-C4 alkynyl, and C2-C4 alkynyloxy groups; when substituted, the substituent is fluorine.

[0034] In some embodiments, R1 and R3 are independently selected from substituted or unsubstituted C1-C6 alkyl groups and substituted or unsubstituted C1-C6 alkoxy groups, and R2 and R4 are independently selected from substituted or unsubstituted C2-C6 alkenyl groups, substituted or unsubstituted C2-C6 alkenyloxy groups, substituted or unsubstituted C2-C6 alkynyl groups, and substituted or unsubstituted C2-C6 alkynyloxy groups. When substituted, the substituent is independently selected from halogens. In some embodiments, the alkyl, alkoxy, alkenyl, alkenyloxy, alkynyl, and alkynyloxy groups are C1-C4 alkyl, C1-C4 alkoxy, C2-C4 alkenyl, C2-C4 alkenyloxy, C2-C4 alkynyl, and C2-C4 alkynyloxy groups; when substituted, the substituent is fluorine.

[0035] In some embodiments, R1, R2, and R3 are independently selected from substituted or unsubstituted C1-C6 alkyl groups, substituted or unsubstituted C1-C6 alkoxy groups, and R4 is selected from substituted or unsubstituted C2-C6 alkenyl groups, substituted or unsubstituted C2-C6 alkenyloxy groups, substituted or unsubstituted C2-C6 alkynyl groups, and substituted or unsubstituted C2-C6 alkynyloxy groups. When substituted, the substituent is independently selected from halogens. In some embodiments, the alkyl, alkoxy, alkenyl, alkenyloxy, alkynyl, and alkynyloxy groups are C1-C4 alkyl, C1-C4 alkoxy, C2-C4 alkenyl, C2-C4 alkenyloxy, C2-C4 alkynyl, and C2-C4 alkynyloxy groups; when substituted, the substituent is fluorine.

[0036] In some embodiments, R1, R2, R3, and R4 are independently selected from substituted or unsubstituted C2-C6 alkenyl, substituted or unsubstituted C2-C6 alkenoxy, substituted or unsubstituted C2-C6 alkynyl, and substituted or unsubstituted C2-C6 alkynoxy. When substituted, the substituent is independently selected from halogens. In some embodiments, the alkenyl, alkenoxy, alkynyl, and alkynoxy groups are C2-C4 alkenyl, C2-C4 alkenoxy, C2-C4 alkynyl, and C2-C4 alkynoxy; when substituted, the substituent is fluorine.

[0037] In some embodiments, R1, R2, R3, and R4 are identical, each selected from substituted or unsubstituted C2-C6 alkenyl, substituted or unsubstituted C2-C6 alkenoxy, substituted or unsubstituted C2-C6 alkynyl, and substituted or unsubstituted C2-C6 alkynoxy. When substituted, the substituent is independently selected from halogens. In some embodiments, the alkenyl, alkenoxy, alkynyl, and alkynoxy groups are C2-C4 alkenyl, C2-C4 alkenoxy, C2-C4 alkynyl, and C2-C4 alkynoxy; when substituted, the substituent is fluorine.

[0038] In some embodiments, the silane compound includes at least one of tetravinylsilane (TVS), trivinylmethylsilane, trivinylethylsilane (ETVS), trivinylfluoromethylsilane (FMTVS), divinyldimethylsilane, divinyldiethylsilane, tetraethynylsilane (TES), triethynylmethylsilane, triethynylethylsilane, diethynyldimethylsilane, and diethynyldiethylsilane.

[0039] In some embodiments, the silane compound includes at least one of tetravinylsilane, trivinylethylsilane, trivinylfluoromethylsilane, and tetraethynylsilane.

[0040] In some embodiments, the electrolyte further includes a second additive. The second additive is not particularly limited, and can be any film-forming additive other than silane compounds. In some embodiments, the second additive includes at least one selected from cyclic carbonates containing carbon-carbon double bonds, fluorinated cyclic carbonates, sulfonates, sulfates, and sulfites. The presence of the second additive does not substantially affect the absolute content of silicon derived from silane compounds in the solid electrolyte interface film on the surface of the positive electrode active material layer.

[0041] In some embodiments, the carbon-carbon double-bonded cyclic carbonate comprises at least one of the compounds shown in Formula II:

[0042] Formula II

[0043] In Formula II, R5 and R6 are independently selected from hydrogen atoms, fluorine atoms, or C1-C6 alkyl groups.

[0044] In some embodiments, R5 and R6 are independently selected from hydrogen atoms, fluorine atoms, or C1-C4 alkyl groups.

[0045] In some embodiments, the cyclic carbonate containing carbon-carbon double bonds includes at least one of vinylene carbonate (VC), methyl vinylene carbonate, or ethyl vinylene carbonate.

[0046] In some embodiments, the fluorinated cyclic carbonate comprises at least one of the compounds shown in Formula III:

[0047] Formula III

[0048] In Equation III, R7, R8, R9, R 10 Independently selected from hydrogen atoms, fluorine atoms, C1-C6 alkyl groups, or fluorinated C1-C6 alkyl groups, and R7, R8, R9, R 10 At least one of them is a fluorine atom or a fluorinated C1-C6 alkyl group, and Q1 is absent or selected from C1-C6 alkylene groups.

[0049] In this application, fluorinated C1-C6 alkyl groups include, but are not limited to, fluorinated methyl, fluorinated ethyl, fluorinated n-propyl, fluorinated isopropyl, fluorinated n-butyl, fluorinated isobutyl, fluorinated tert-butyl, fluorinated n-pentyl, fluorinated isopentyl, and fluorinated n-hexyl. In some embodiments, the fluorinated C1-C6 alkyl groups are selected from monofluoromethyl, difluoromethyl, trifluoromethyl, monofluoroethyl, difluoroethyl, trifluoroethyl, pentafluoroethyl, or hexafluoroisopropyl.

[0050] In some implementations, R7, R8, R9, R 10 Independently selected from hydrogen atoms, fluorine atoms, C1-C4 alkyl groups, or fluorinated C1-C4 alkyl groups, and R7, R8, R9, R 10 At least one of them is a fluorine atom or a fluorinated C1-C4 alkyl group, and Q1 is absent or selected from C1-C4 alkylene groups.

[0051] In some implementations, R7, R8, R9, R 10 Independently selected from hydrogen atom, fluorine atom, methyl, ethyl, trifluoromethyl, 2,2,2-trifluoroethyl, and R7, R8, R9, R 10 At least one of them is a fluorine atom, and Q1 is either absent or selected from methylene or ethylene.

[0052] In some embodiments, the fluorinated cyclic carbonate includes at least one of fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), and trifluoropropylene carbonate (TFPC).

[0053] In some embodiments, the sulfonate ester includes at least one of the compounds shown in Formula IV-1.

[0054] Formula IV-1

[0055] In Formula IV-1, Q2 and Q3 are independently selected from C1-C6 alkylene groups.

[0056] In some embodiments, Q2 and Q3 are independently selected from C1-C4 alkylene groups, such as methylene, ethylene, or propylene.

[0057] In some embodiments, the sulfonate includes at least one of methylene disulfonate (MMDS), ethylene disulfonate, and propylene disulfonate.

[0058] In some embodiments, the sulfonate ester includes at least one of the compounds shown in formula IV-2.

[0059] Formula IV-2

[0060] In equation IV-2, R11 R 12 Q4 is independently selected from hydrogen atoms or C1-C6 alkyl groups, and Q4 is selected from C1-C6 alkylene groups or C2-C6 alkenyl groups.

[0061] In some implementations, R 11 R 12 Q4 is independently selected from hydrogen atoms or C1-C4 alkyl groups, and Q4 is selected from C1-C4 alkylene groups or C2-C4 alkenyl groups.

[0062] In some embodiments, the sulfonate includes at least one of 1,3-propanesulfonyl lactone (PS), 1-propylene-1,3-sulfonyl lactone (PST), and 1,4-butanesulfonyl lactone (BS).

[0063] In some embodiments, the sulfate ester includes at least one of the compounds represented by formula V.

[0064] Formula V

[0065] In formula V, R 13 R 14 R 15 R 16 It is independently selected from hydrogen atoms or C1-C6 alkyl groups, and Q5 is absent or selected from C1-C6 alkylene groups.

[0066] In some implementations, R 13 R 14 R 15 R 16 Q5 is independently selected from hydrogen atoms or C1-C4 alkyl groups, and Q5 is absent or selected from C1-C4 alkylene groups.

[0067] In some embodiments, the sulfate ester includes at least one of vinyl sulfate (DTD), 4-methyl ethylene sulfate (PCS), 4-ethyl ethylene sulfate (PES), 4-propyl ethylene sulfate (PEGLST), and propylene sulfate (TS).

[0068] In some embodiments, the sulfite comprises at least one of the compounds shown in Formula VI.

[0069] Style VI

[0070] In equation VI, R 17 R 18 R 19 R 20 Q6 is independently selected from hydrogen atoms or C1-C6 alkyl groups, and Q6 is absent or selected from C1-C6 alkylene groups.

[0071] In some implementations, R17 R 18 R 19 R 20 Q6 is independently selected from hydrogen atoms or C1-C4 alkyl groups, and Q6 is absent or selected from C1-C4 alkylene groups.

[0072] In some embodiments, the sulfite includes ethylene sulfite (DTO).

[0073] In some embodiments, the second additive includes at least one selected from vinylene carbonate, methyl vinylene carbonate, ethyl vinylene carbonate, fluoroethylene carbonate, difluoroethylene carbonate, trifluoropropylene carbonate, methylene disulfonate, ethyl disulfonate, propylene disulfonate, 1,3-propane sulpholactone, 1-propylene-1,3-sulfonate lactone, 1,4-butane sulpholactone, vinyl sulfate, 4-methyl ethylene sulfate, 4-ethyl ethylene sulfate, 4-propyl ethylene sulfate, propylene sulfate, and ethylene sulfite.

[0074] In some embodiments, the second additive is selected from at least one of vinylene carbonate, fluoroethylene carbonate, methyl disulfonate, 1,3-propane sulpholactone, 1-propylene-1,3-sulfonate lactone, 1,4-butane sulpholactone, and vinyl sulfate.

[0075] In some embodiments, the mass ratio of the first additive to the second additive is 1:0.25 to 1:20. In some embodiments, the mass ratio of the first additive to the second additive is 1:0.25, 1:0.5, 1:0.75, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, 1:5.5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19, 1:20, or a range of any two of these values. In some embodiments, the mass ratio of the first additive to the second additive is 1:0.25 to 1:10. In some embodiments, the mass ratio of the first additive to the second additive is 1:0.25 to 1:8.

[0076] In some embodiments, the electrolyte further includes a lithium salt. In some embodiments, the lithium salt includes at least one selected from lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium trifluoromethanesulfonyl (LiOTf), lithium bis(fluoromalonic acid)borate (LiBOB), lithium bis(fluoromalonic acid)borate (LiBFMB), and lithium difluorooxalateborate (LiDFOB).

[0077] In some embodiments, the electrolyte further includes a solvent. In some embodiments, the solvent includes at least one selected from chain carbonates, cyclic carbonates, and carboxylic acid esters.

[0078] In some embodiments, the chain carbonate includes at least one selected from dimethyl carbonate, diethyl carbonate, dipropyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, and fluorinated chain carbonates. In some embodiments, the cyclic carbonate includes at least one selected from ethylene carbonate, propylene carbonate, and butenyl carbonate. In some embodiments, the carboxylic acid ester includes at least one selected from methyl formate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, and fluorinated carboxylic acid esters.

[0079] In some embodiments, the solvent comprises chain carbonates and / or cyclic carbonates, wherein the mass content of the chain carbonates and / or cyclic carbonates is 90% or more, for example, 95% or more, or 98% or more, based on the mass of the solvent. In some embodiments, the solvent does not include ethers.

[0080] In some embodiments, the positive electrode active material includes at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide.

[0081] In some embodiments, the positive electrode active material comprises at least one selected from lithium-nickel transition metal oxides. In some embodiments, the lithium-nickel transition metal oxide has the chemical formula LiNi. m Co n A (1-m-n) As shown in O2, A is selected from at least one of manganese, aluminum, magnesium, zirconium, strontium, yttrium, lanthanum, molybdenum, silver, niobium, iron, titanium, copper, zinc, chromium, calcium, barium, and tungsten, with 0.5 ≤ m ≤ 1, 0 ≤ n ≤ 0.5, and m + n ≤ 1. In some embodiments, the chemical formula of the lithium nickel transition metal oxide is as shown in LiNi. m Co n A (1-m-n) As shown in O2, A is selected from at least one of manganese, aluminum, magnesium, zirconium, strontium, yttrium, lanthanum, molybdenum, silver, niobium, chromium and calcium, with 0.5≤m≤1, 0≤n≤0.5, and m+n≤1.

[0082] In some implementations, m is a range of 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, or any combination of these values. In some implementations, n is a range of 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, or any combination of these values.

[0083] In some embodiments, the lithium nickel transition metal oxide includes at least one of NCM523, NCM622, NCM811, Ni90 (i.e., NCM90), Ni92 (i.e., NCM92), or Ni95 (i.e., NCM900).

[0084] In some embodiments, the lithium-nickel transition metal oxide has the chemical formula LiNi. m Co n A (1-m-n) As shown in O2, A is selected from at least one of manganese, aluminum, magnesium, zirconium, strontium, yttrium, lanthanum, molybdenum, silver, niobium, iron, titanium, copper, zinc, chromium, calcium, barium, and tungsten, with 0.7 ≤ m ≤ 1, 0 ≤ n ≤ 0.3, and m + n ≤ 1. In some embodiments, the chemical formula of the lithium nickel transition metal oxide is as shown in LiNi. m Co n A (1-m-n) As shown in O2, A is selected from at least one of manganese, aluminum, magnesium, zirconium, strontium, yttrium, lanthanum, molybdenum, silver, niobium, chromium and calcium, with 0.7≤m≤1, 0≤n≤0.3, and m+n≤1.

[0085] In some embodiments, the lithium nickel transition metal oxide includes at least one of NCM811, Ni90, Ni92, or Ni95.

[0086] In some embodiments, the lithium-nickel transition metal oxide may further include a coating layer. The coating layer may, exemplarily, comprise one or more of lithium aluminate, aluminum oxide, lithium borate, or lithium boride.

[0087] In some embodiments, the positive electrode active material may also include at least one phosphate compound, the chemical formula of which is LiMn k B (1-k) As shown in PO4, where 0 ≤ k ≤ 1, and B is selected from at least one of iron, cobalt, magnesium, calcium, zinc, chromium, and lead. In some embodiments, k is a range of 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, or any combination of these values. In some embodiments, the phosphate compound includes lithium iron phosphate, LiMn... 0.6 Fe 0.4 PO4 or LiMn 0.8 Fe 0.2 At least one of PO4.

[0088] In some embodiments, the positive electrode further includes a binder and a conductive agent. In some embodiments, the binder includes, but is not limited to, polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, and polyvinylpyrrolidone. In some embodiments, the conductive agent includes, but is not limited to, carbon nanotubes, carbon black (e.g., conductive carbon black SP), natural graphite, artificial graphite, acetylene black, Ketjen black, and carbon fiber.

[0089] In some embodiments, the mass percentage of the active material in the positive electrode active material layer is between 95% and 99%, for example, 95%, 96%, 97%, 98%, 99%, or any combination of these values. In some embodiments, the mass percentage of the conductive agent in the positive electrode active material layer is between 0.5% and 5%, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or any combination of these values.

[0090] In some embodiments, the average density of the active material layer of the positive electrode is 4 g / cm³. 3 -5 g / cm 3 If the average density of the active material layer is too high, the porosity of the corresponding positive electrode will be large, and the conductivity of the electrode will also decrease, which will reduce the utilization rate of the secondary battery and affect its electrochemical performance and energy density. If the average density of the active material layer is too low, the porosity of the corresponding positive electrode will be small, the ability of the positive electrode to absorb electrolyte will be reduced, the electrolyte will be difficult to wet, the polarization of the secondary battery will increase during cycling, and thus affect its cycle performance.

[0091] In some embodiments, the average density of the active material layer of the positive electrode is 4 g / cm³. 3 4.1 g / cm 3 4.2 g / cm 3 4.3 g / cm 3 4.4 g / cm 3 4.5 g / cm 3 4.6 g / cm 3 4.7 g / cm 3 4.8 g / cm 3 4.9 g / cm 3 5 g / cm 3 Or a range of any two of these values. In some embodiments, the average density of the active material layer of the positive electrode is 4.2 g / cm³. 3 -4.8 g / cm 3 .

[0092] In some embodiments, the resistance of the positive electrode is 15 mΩ-40 mΩ. If the resistance of the positive electrode is too high, its electronic conductivity is poor, which is not conducive to high-current charging and discharging, results in low utilization of active materials, and also affects the film formation efficiency of the CEI film, thereby degrading the battery's electrical performance. If the resistance of the positive electrode is too low, its electronic conductivity is good, corresponding to a higher content of positive electrode conductive agent and a lower proportion of active materials, which reduces the battery's energy density and decreases its capacity.

[0093] In some embodiments, the resistance of the positive electrode is 15 mΩ, 17 mΩ, 19 mΩ, 20 mΩ, 21 mΩ, 22 mΩ, 23 mΩ, 24 mΩ, 25 mΩ, 26 mΩ, 27 mΩ, 28 mΩ, 29 mΩ, 30 mΩ, 32 mΩ, 34 mΩ, 36 mΩ, 38 mΩ, 40 mΩ, or any combination of these values. In some embodiments, the resistance of the positive electrode is 20 mΩ-30 mΩ. In this application, the resistance of the positive electrode can be adjusted using conventional techniques in the art, depending on the characteristics of the selected active material and conductive agent, such as adjusting the content of the active material and conductive agent, and controlling the electrode coating and rolling processes.

[0094] In some embodiments, the positive electrode sheet further includes a positive current collector, which can be a metal foil or a composite current collector. For example, aluminum foil can be used. The composite current collector can be formed by forming a metallic material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer substrate.

[0095] In some embodiments, the negative electrode includes a negative electrode active material, which includes a silicon-based material. The silicon-based material includes at least one of silicon, silicon alloys, silicon oxides, and silicon-carbon compounds. In some embodiments, the silicon-based material includes silicon oxides and / or silicon-carbon compounds.

[0096] In some embodiments, the negative electrode active material further includes a mixture of at least one material selected from carbon-based materials, tin-based materials, phosphorus-based materials, and metallic lithium. The carbon-based material includes at least one selected from graphite, soft carbon, hard carbon, carbon nanotubes, and graphene. The tin-based material includes at least one selected from tin, tin oxide, and tin alloys. The phosphorus-based material includes phosphorus and / or phosphorus complexes.

[0097] In some embodiments, the mass content (g%) of the silicon-based material, based on the mass of the negative electrode active material, satisfies: 8 ≤ g ≤ 100. In some embodiments, g is a range of 10, 12, 14, 16, 18, 20, 22, 25, 28, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, or any combination of these values. In some embodiments, 10 ≤ g ≤ 50. In other embodiments, 12 ≤ g ≤ 35.

[0098] In some embodiments, the negative electrode sheet further includes a binder and a conductive agent. In some embodiments, the binder includes, but is not limited to, styrene-butadiene rubber, acrylated styrene-butadiene rubber, polyacrylic acid, polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, and polyvinylpyrrolidone. In some embodiments, the conductive agent includes, but is not limited to, carbon nanotubes, natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, and carbon fiber.

[0099] In some embodiments, the negative electrode sheet further includes a negative current collector, which includes: copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, or any combination thereof.

[0100] In some embodiments, a separator is provided between the positive and negative electrode plates to prevent short circuits. The material and shape of the separator used in the embodiments of this application are not particularly limited, and can be any technology disclosed in the prior art. In some embodiments, the separator comprises a polymer or inorganic material formed from a material stable to the electrolyte of this application.

[0101] For example, the diaphragm may include a substrate layer and a surface treatment layer. The substrate layer is a nonwoven fabric, membrane, or composite membrane with a porous structure, and the material of the substrate layer includes at least one selected from polyethylene, polypropylene, polyethylene terephthalate, polyimide, or aramid. Specifically, a polypropylene porous membrane, a polyethylene porous membrane, a polypropylene nonwoven fabric, a polyethylene nonwoven fabric, or a polypropylene-polyethylene-polypropylene porous composite membrane may be selected.

[0102] A surface treatment layer is disposed on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing polymers and inorganic substances.

[0103] The inorganic layer comprises inorganic particles and a binder. The inorganic particles include at least one of alumina, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, or barium sulfate. The binder includes at least one of polyvinylidene fluoride, a copolymer of polyvinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene, or polyhexafluoropropylene.

[0104] The polymer layer contains a polymer, the polymer material of which includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polyvinylidene fluoride, or poly(vinylidene fluoride-hexafluoropropylene).

[0105] In some embodiments, the method for preparing the secondary battery includes providing electrode assemblies, liquid injection, encapsulation, and formation. In some embodiments, the formation temperature is 40°C to 50°C. In some embodiments, the formation temperature is a range of 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C, 50°C, or any combination of these values.

[0106] In some embodiments, the formation pressure is from 150 kgf to 750 kgf. In some embodiments, the formation temperature is a range of 150 kgf, 160 kgf, 170 kgf, 180 kgf, 190 kgf, 200 kgf, 210 kgf, 220 kgf, 230 kgf, 240 kgf, 250 kgf, 260 kgf, 270 kgf, 280 kgf, 290 kgf, 300 kgf, 320 kgf, 350 kgf, 380 kgf, 400 kgf, 420 kgf, 450 kgf, 480 kgf, 500 kgf, 520 kgf, 550 kgf, 580 kgf, 600 kgf, 620 kgf, 650 kgf, 680 kgf, 700 kgf, 720 kgf, 750 kgf, or any combination of these values. In some embodiments, the formation pressure is from 150 kgf to 300 kgf.

[0107] In some embodiments, the formation charging current is 0.02C-0.33C, and the formation discharging current is 0.05C-0.5C. In some embodiments, the formation charging current is 0.02C, 0.03C, 0.05C, 0.07C, 0.09C, 0.1C, 0.12C, 0.14C, 0.16C, 0.18C, 0.2C, 0.22C, 0.24C, 0.26C, 0.28C, 0.3C, 0.32C, 0.33C, or a range of any two of these values. In some embodiments, the formation charging current is 0.03C-0.2C. In some embodiments, the formation discharge current is 0.05C, 0.07C, 0.1C, 0.12C, 0.15C, 0.18C, 0.2C, 0.22C, 0.25C, 0.28C, 0.3C, 0.32C, 0.35C, 0.38C, 0.4C, 0.42C, 0.45C, 0.48C, 0.5C, or any combination of these values. In some embodiments, the formation discharge current is 0.1C-0.3C.

[0108] In some embodiments, the charging voltage of the formation is 4.0V-4.4V, for example 4.0V, 4.1V, 4.2V, 4.3V, or 4.4V. In some embodiments, the discharging voltage of the formation is 2.8V-3.2V, for example 2.8V, 2.9V, 3.0V, 3.1V, or 3.2V.

[0109] In some embodiments, the formation includes: charging to 4.0V-4.4V, for example 4.2V, at a temperature of 40°C-50°C, for example 45°C, and a pressure of 150kgf-300kgf, for example 210kgf, with a current of 0.03C-0.08C, for example 0.05C, allowing it to stand, then charging to 4.0V-4.4V at 0.08C-0.2C, and then discharging to 2.8V-3.2V, for example 3.0V, at 0.1C-0.3C, for example 0.2C.

[0110] In some embodiments, the secondary battery undergoes formation. In some embodiments, the solid electrolyte interphase (CEI) membrane is obtained through the formation of the secondary battery. During the formation process, the silane compound is oxidized on the surface of the positive electrode active material to form a CEI membrane, which inhibits the continuous reaction between the electrolyte and the positive electrode active material. After multiple cycles, the absolute silicon content in the CEI membrane will differ slightly from the absolute silicon content in the CEI membrane after formation, but the relative content, i.e., the mass percentage of silicon in the CEI membrane, will still be between 0.8% and 8%.

[0111] In some embodiments, the secondary battery is a lithium secondary battery or a sodium secondary battery. In some embodiments, the lithium secondary battery includes, but is not limited to, a lithium metal secondary battery, a lithium-ion secondary battery, a lithium polymer secondary battery, or a lithium-ion polymer secondary battery.

[0112] In some embodiments, the secondary battery may include an outer packaging, which may be a rigid shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging may also be a soft pack, such as a pouch. The soft pack may be made of plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).

[0113] In some embodiments, the shape of the secondary battery is not particularly limited; it can be cylindrical, square, or any other arbitrary shape.

[0114] In some embodiments, this application also provides a battery module. This battery module includes the aforementioned secondary battery. The battery module of this application uses the aforementioned secondary battery, and therefore has at least the same advantages as the aforementioned secondary battery. The battery module of this application can contain multiple secondary batteries, and the specific number can be adjusted according to the application and capacity of the battery module.

[0115] In some embodiments, this application also provides a battery pack that includes the aforementioned battery modules. The number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack.

[0116] II. Apparatus

[0117] This application also provides an apparatus comprising at least one of the above-described secondary batteries, battery modules, or battery packs.

[0118] In some embodiments, the device includes, but is not limited to, electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and energy storage systems. To meet the device's requirements for high power and high energy density in secondary batteries, battery packs or battery modules may be used.

[0119] In other embodiments, the device can be a mobile phone, tablet computer, laptop computer, etc. This device typically requires a slim and lightweight design and can use a rechargeable battery as its power source.

[0120] Example

[0121] Unless otherwise specified, all materials and reagents used in this application are commercially available.

[0122] Test methods

[0123] 1. Determination of the average density of the active material layer of the positive electrode sheet

[0124] The average density of the active material layer is calculated using the formula: 1 / (mass percentage of active material / density of active material + mass percentage of conductive agent / density of conductive agent + mass percentage of binder / density of binder), where the mass percentage of each component is the percentage of the mass of each component to the total mass of the active material layer.

[0125] 2. Resistance measurement of the positive electrode plate

[0126] The resistance of the positive electrode was tested using a two-probe method with a BER2500 (IEST Yuaneng Technology) device. Before testing, the prepared positive electrode was cut into test samples with a diameter of 14 mm. During testing, the terminals were placed at both ends of the positive electrode, a pressure of 25 MPa was applied, and the current across the sample was collected using the input AC voltage signal to obtain the sample resistance.

[0127] 3. Measurement of battery impedance

[0128] The lithium-ion battery was discharged at 25±2℃ with a constant current of 1C to 2.5V, then charged with a constant current of 0.5C to 4.25V, and then charged with a constant voltage of 0.05C at 4.25V. It was then discharged again with a constant current of 1C to 50% SOC, allowed to stand for 60 min, and the voltage U1 at the end of the standing period was recorded. Next, it was discharged with a constant current of 2C for 10 s, and the voltage U2 at the end of the discharge period was recorded. The 2C current was recorded as I, and the battery was allowed to stand for 60 min. The discharge DCR at 50% SOC was calculated using the formula DCR=(U1-U2) / I.

[0129] 4. Battery high-temperature cycle performance test

[0130] At 45°C, the lithium-ion battery was charged at a constant current of 0.5C to 4.25V, then charged at a constant voltage of 4.25V to 0.05C, and finally discharged at a constant current of 1C to 2.5V. After 400 charge-discharge cycles, the capacity retention rate after the 400th cycle at 45°C was calculated using the following formula: Discharge capacity after 400 cycles / Discharge capacity of the first cycle × 100%.

[0131] 5. Determination of the thickness change rate of batteries stored at 60℃

[0132] The lithium-ion battery was discharged at 25°C with a constant current of 1C to 2.5V, then charged at a constant current of 0.5C to 4.25V, and then charged at a constant voltage of 4.25V to 0.05C. The thickness of the battery at this point was measured using a PPG soft-pack battery thickness gauge and recorded as 'a'. The battery was then placed in an oven and stored at 60°C with a constant voltage of 4.25V for 30 days. The thickness after 30 days was recorded as 'b'. The formula for calculating the thickness expansion rate is: (ba) / a × 100%.

[0133] 6. Determination of silicon content in CEI membranes

[0134] The silicon content in the CEI film was tested using EDS, and the specific testing steps are as follows: The lithium-ion battery was discharged to 2.5 V at a current of 0.1C, and the electrode sheets were obtained by disassembling the lithium-ion battery in an argon-filled glove box. The obtained positive electrode sheets were cut into pieces with an area of ​​approximately 20 mm². 2 Test samples of various sizes were immersed and cleaned with low-boiling-point dimethyl carbonate (DMC) solvent for half an hour to remove residual electrolyte on the electrode surface. After the DMC solvent had completely evaporated, the samples were quickly transferred to the conductive adhesive on the EDS sample stage, with the surface of the positive electrode active material layer facing upwards, and any dust on the sample surface was removed with a syringe. Samples were then injected for detection at a depth of approximately 500 nm to 1 µm to determine the elemental content of Be to U in the CEI film and to calculate the mass percentage of silicon in the CEI film. The energy resolution was 132 eV.

[0135] 7. Determination of nickel content on the negative electrode after 400 cycles

[0136] The nickel content on the negative electrode was measured using inductively coupled plasma optical emission spectrometry (ICP). The specific testing procedure is as follows: Before testing, the lithium-ion battery was charged at a constant current of 0.5C to 4.25V at 45℃, then charged at a constant voltage of 4.25V to 0.05C, and then discharged at a constant current of 1C to 2.5V. After 400 charge-discharge cycles, the lithium-ion battery was disassembled in an argon-filled glove box to obtain the negative electrode. The disassembled negative electrode was soaked in DMC solvent for half an hour to remove residual electrolyte on the electrode surface and eliminate the influence of electrolyte. After the DMC solvent completely evaporated, the negative electrode powder was collected for later use. Weigh 0.05 g (accurate to 0.00001 g) of the collected negative electrode powder and place it in a 50 mL beaker. Add 8.0 mL of 6 mol / L hydrochloric acid, then heat the beaker at a low temperature on an electric furnace to dissolve the powder. After the powder is basically dissolved, add 5 drops of hydrogen peroxide and a small amount of water, and heat until the solution stops bubbling. Remove the beaker and cool. Transfer the cooled solution to a 100 mL volumetric flask and perform a blank experiment (the blank experiment is a control experiment without adding negative electrode powder but with all other conditions the same). The content of transition metal nickel on the surface of the negative electrode active material layer can be obtained by the above test method, in ppm. For cells that fail before 400 cycles, the cells corresponding to the cycle number when their capacity first decays to below 60% are used for ICP testing.

[0137] Example 1

[0138] The preparation steps for the positive electrode sheet are as follows: Mix the positive electrode active material LiNi at a mass ratio of 96:2:2. 0.6 Co 0.2 Mn 0.2 O2, conductive agent carbon black, and binder polyvinylidene fluoride are dispersed in N-methyl-2-pyrrolidone to obtain a positive electrode slurry. The positive electrode slurry is uniformly coated on both sides of a 12 µm thick aluminum foil current collector, and then dried, rolled, and slit to obtain a positive electrode sheet.

[0139] The negative electrode preparation steps are as follows: a silicon-oxygen-graphite composite (the mass ratio of silicon-oxygen to graphite is 10:90), conductive agent acetylene black, binder styrene-butadiene rubber, thickener sodium carboxymethyl cellulose and binder polyacrylic acid are mixed in a mass ratio of 95:2:1.5:1:0.5 and then dispersed in deionized water to obtain a negative electrode slurry. The negative electrode slurry is coated on both sides of an 8 µm thick copper foil current collector, and after drying, rolling and slitting, a negative electrode sheet is obtained.

[0140] The diaphragm is a three-layer composite PP / PE / PP membrane.

[0141] Electrolyte preparation: In an argon-protected glove box (H2O < 0.1 ppm, O2 < 0.1 ppm), ethylene carbonate (EC), diethyl carbonate (DEC), and methyl ethyl carbonate (EMC) were mixed in a mass ratio of EC:DEC:EMC = 2:3:5. Lithium hexafluorophosphate (LiPF6) was added to prepare a solution with a lithium salt concentration of 1 mol / L. Then, the first additive, silane compound (TVS), and the second additive (FEC) in the amounts shown in Table 1 were added. After stirring evenly, the lithium-ion battery electrolyte of Example 1 was obtained.

[0142] Preparation of lithium-ion batteries: The prepared positive electrode, separator, and negative electrode are stacked in sequence, with the separator positioned between the positive and negative electrodes, and wound to obtain a bare cell. The bare cell is placed in an aluminum-plastic film outer packaging, and after thorough drying, it is injected with the prepared lithium-ion battery electrolyte. After the battery is placed at 45°C for 48 hours, formed in a high-temperature fixture (formation conditions are: temperature 45°C, pressure 210 kgf, charging to 4.2 V at 0.05C and resting for 60 minutes, then charging to 4.2 V at 0.1C, then discharging to 3.0 V at 0.2C, and repeating this process twice), and then sealed twice, conventional capacity testing is performed to finally obtain a lithium-ion battery with a rated capacity of ~4Ah.

[0143] Examples 2 to 16 and Comparative Examples 1 to 5

[0144] Examples 2 to 16 and Comparative Examples 1 to 5 were based on Example 1 and were achieved by adjusting the types of the first additive silane compound and the second additive in the electrolyte, their mass ratio, the type of positive electrode active material, the nickel content in the positive electrode active material layer relative to each g of the first additive silane compound, the resistance of the positive electrode sheet (which was achieved by adjusting the type and proportion of the positive electrode active material, the type and proportion of the conductive agent, etc.), and the average density of the active material layer of the positive electrode sheet (which was achieved by adjusting the type and proportion of the positive electrode active material, the type and proportion of the conductive agent, etc.). Specific adjustment measures and detailed data are shown in Table 1.

[0145] Table 1

[0146]

[0147] The test results of lithium-ion batteries in Examples 1-16 and Comparative Examples 1-5 are shown in Table 2.

[0148] Table 2

[0149]

[0150] * indicates that the battery's capacity retention rate was already below 60% in one of the cycles before the 400th cycle.

[0151] While some exemplary embodiments of this application have been described and illustrated, this application is not limited to the disclosed embodiments. Rather, those skilled in the art will recognize that modifications and changes may be made to the described embodiments without departing from the spirit and scope of this application as described in the appended claims.

Claims

1. A secondary battery, comprising a positive electrode, a negative electrode, and an electrolyte, wherein, The electrolyte includes a first additive, which is a silane compound; The positive electrode includes a positive active material layer and a solid electrolyte interface film located on the surface of the positive active material layer. Energy dispersive spectroscopy (EDS) analysis shows that the mass percentage of silicon in the solid electrolyte interface film is A%. The positive electrode active material layer comprises a lithium nickel transition metal oxide, and the content of the silane compound is 1 g relative to B g of nickel in the positive electrode active material layer; Wherein, 0.2≤100×A / B≤10.

2. The secondary battery according to claim 1, characterized in that, 0.5≤100×A / B≤8.

3. The secondary battery according to claim 1 or 2, characterized in that, 0.8≤A≤8, and / or, 60≤B≤700.

4. The secondary battery according to claim 1 or 2, characterized in that, 2≤A≤7, and / or, 100≤B≤600.

5. The secondary battery according to claim 1 or 2, characterized in that, The silane compound includes at least one of the compounds represented by Formula I. Equation I In Formula I, R1, R2, R3, and R4 are independently selected from substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C1-C6 alkoxy, substituted or unsubstituted C2-C6 alkenyl, substituted or unsubstituted C2-C6 alkenyloxy, substituted or unsubstituted C2-C6 alkynyl, and substituted or unsubstituted C2-C6 alkynyloxy, and at least one of R1, R2, R3, and R4 is selected from substituted or unsubstituted C2-C6 alkenyl, substituted or unsubstituted C2-C6 alkenyloxy, substituted or unsubstituted C2-C6 alkynyl, and substituted or unsubstituted C2-C6 alkynyloxy. When substituted, the substituent is independently selected from halogens.

6. The secondary battery according to claim 5, characterized in that, The silane compound includes at least one of tetravinylsilane, trivinylmethylsilane, trivinylethylsilane, trivinylfluoromethylsilane, divinyldimethylsilane, divinyldiethylsilane, tetraethynylsilane, triethynylmethylsilane, triethynylethylsilane, diethynyldimethylsilane, and diethynyldiethylsilane.

7. The secondary battery according to claim 1 or 2, characterized in that, The secondary battery satisfies at least one of the following conditions: (a) The positive electrode active material includes those selected from LiNi as shown in the formula. m Co n A (1-m-n) O2 represents at least one of lithium nickel transition metal oxides, wherein A is selected from at least one of manganese, aluminum, magnesium, zirconium, strontium, yttrium, lanthanum, molybdenum, silver, niobium, iron, titanium, copper, zinc, chromium, calcium, barium, and tungsten, and 0.5≤m≤1, 0≤n≤0.5, m+n≤1; (b) The electrolyte includes a second additive selected from at least one of cyclic carbonates containing carbon-carbon double bonds, fluorinated cyclic carbonates, sulfonates, sulfates and sulfites; (c) The solid electrolyte interface membrane is a non-artificial membrane.

8. The secondary battery according to claim 7, characterized in that, The secondary battery satisfies at least one of the following conditions: (d) The positive electrode active material includes those selected from LiNi as shown in the formula. m Co n A (1-m-n) O2 represents at least one of lithium nickel transition metal oxides, wherein A is selected from at least one of manganese, aluminum, magnesium, zirconium, strontium, yttrium, lanthanum, molybdenum, silver, niobium, chromium and calcium, and 0.7≤m≤1, 0≤n≤0.3, m+n≤1; (e) The second additive comprises at least one of vinylene carbonate, methyl vinylene carbonate, ethyl vinylene carbonate, fluoroethylene carbonate, difluoroethylene carbonate, trifluoropropylene carbonate, methylene disulfonate, ethyl disulfonate, propylene disulfonate, 1,3-propane sulpholactone, 1-propylene-1,3-sulfonate lactone, 1,4-butane sulpholactone, vinyl sulfate, 4-methyl ethylene sulfate, 4-ethyl ethylene sulfate, 4-propyl ethylene sulfate, propylene sulfate, and ethylene sulfite. (f) The mass ratio of the first additive to the second additive is 1:0.25-1:20; (g) The solid electrolyte interface film is formed by the reaction of the positive electrode active material and the electrolyte.

9. The secondary battery according to claim 8, characterized in that, The secondary battery satisfies at least one of the following conditions: (h) The average density of the active material layer of the positive electrode sheet is 4 g / cm³. 3 -5 g / cm 3 ; (i) The resistance of the positive electrode is 15 mΩ-40 mΩ; (j) The negative electrode sheet includes an active material selected from silicon-based materials, wherein the silicon-based material includes at least one of silicon, silicon alloy, silicon oxide and silicon carbide, and the mass content of the silicon-based material in g% based on the mass of the negative electrode active material satisfies: 8 ≤ g ≤ 100; (k) The secondary battery is formed.

10. An electrical device comprising a secondary battery as described in any one of claims 1-9.

Citation Information

Patent Citations

  • Protective layers for electrodes and electrochemical cells

    CN109155441A

  • High-voltage electrolyte and lithium ion battery

    CN113725483A